Generation Process of Large‐Amplitude Upper‐Band Chorus Emissions Observed by Van Allen Probes. Issue 5 (18th May 2018) - Kubota, Yuko; Omura, Yoshiharu; Kletzing, Craig; Reeves, Geoffrey
Abstract: We analyze large‐amplitude upper‐band chorus emissions measured near the magnetic equator by the Electric and Magnetic Field Instrument Suite and Integrated Science instrument package on board the Van Allen Probes. In setting up the parameters of source electrons exciting the emissions based on theoretical analyses and observational results measured by the Helium Oxygen Proton Electron instrument, we calculate threshold and optimum amplitudes with the nonlinear wave growth theory. We find that the optimum amplitude is larger than the threshold amplitude obtained in the frequency range of the chorus emissions and that the wave amplitudes grow between the threshold and optimum amplitudes. In the frame of the wave growth process, the nonlinear growth rates are much greater than the linear growth rates. Key Points: Observations by Van Allen Probes show that the upper‐band chorus emissions exist both inside and outside the plasmasphere The densities and thermal velocities of electrons generating the chorus emissions are evaluated from HOPE particle data Observed chorus amplitude and frequency ranges agree with the nonlinear wave growth theory